10.1016/s1541-9800(11)70534-8 (CrossRef Listing of Deleted DOIs, 2000)
Objective To evaluate the physiological response following vasopressin initiation and identify factors associated with mortality in extremely preterm infants with refractory cardiopulmonary instability. Study design Retrospective cohort study of infants born at less than 29 weeks' gestation who received vasopressin. Physiological responses and mortality were evaluated using multivariate logistic regression and receiver operating characteristic analyses. Results The cohort included 87 infants, of whom 60 (69.0%) died before discharge. Prior to vasopressin initiation, non-survivors had lower pH (7.20 [7.07-7.26] vs. 7.25 [7.21-7.30]; p = 0.009), higher lactate concentrations (5.6 vs. 1.1 mmol/L; p = 0.001), and higher oxygen saturation index (14.7 vs. 12.0; p = 0.022). Following vasopressin initiation, mean blood pressure increased from 29.0 to 39.0 mmHg at 24 h (p < 0.001), while FiO 2 requirements, oxygenation indices, and lactate concentrations decreased. Lower pre-treatment pH (adjusted OR 0.53, 95% CI 0.33-0.87; p = 0.012), higher oxygen saturation index (adjusted OR 1.10, 95% CI 1.02-1.19; p = 0.017), and higher lactate concentration (adjusted OR 1.62, 95% CI 1.04-2.54; p = 0.035) were independently associated with mortality. Lactate showed the strongest discrimination for mortality (AUC 0.85, 95% CI 0.69-0.97). Conclusion Vasopressin initiation was associated with improved physiological markers. Mortality was associated more strongly with impaired perfusion and oxygenation severity than with blood pressure alone.